Integration Questions

Question Number 103198 by Dwaipayan Shikari last updated on 13/Jul/20

$$\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({logx}\right){dx} \\$$

Commented by Dwaipayan Shikari last updated on 13/Jul/20

$${sinx}=\frac{{e}^{{ix}} −{e}^{−{ix}} }{\mathrm{2}{i}} \\$$$${sin}\left({logx}\right)=\frac{{x}^{{i}} −{x}^{−{i}} }{\mathrm{2}{i}} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} \frac{{x}^{{i}} −{x}^{−{i}} }{\mathrm{2}{i}}{dx}=\frac{\mathrm{1}}{\mathrm{2}{i}}\int{x}^{{i}} −{x}^{−{i}} {dx}=\frac{\mathrm{1}}{\mathrm{2}{i}}.\left[\left(\frac{{x}^{{i}+\mathrm{1}} }{{i}+\mathrm{1}}−\frac{{x}^{−{i}+\mathrm{1}} }{\mathrm{1}−{i}}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} \\$$$$=\frac{\mathrm{1}}{\mathrm{2}{i}}\left(\frac{\mathrm{1}}{{i}+\mathrm{1}}−\frac{\mathrm{1}}{\mathrm{1}−{i}}\right)=−\frac{\mathrm{1}}{\mathrm{2}} \\$$$$\boldsymbol{\mathrm{Is}}\:\boldsymbol{\mathrm{it}}\:\boldsymbol{\mathrm{true}}??????? \\$$

Answered by OlafThorendsen last updated on 13/Jul/20

$$\mathrm{I}\:=\:\int_{\mathrm{0}} ^{\mathrm{1}} \mathrm{sin}\left(\mathrm{ln}{x}\right){dx} \\$$$${x}\:=\:{e}^{{u}} \:\Rightarrow\:{dx}\:=\:{e}^{{u}} {du} \\$$$$\mathrm{I}\:=\:\int_{−\infty} ^{\mathrm{0}} \mathrm{sin}{u}.{e}^{{u}} {du} \\$$$$\mathrm{I}\:=\:\int_{−\infty} ^{\mathrm{0}} \frac{{e}^{{iu}} −{e}^{−{iu}} }{\mathrm{2}{i}}{e}^{{u}} {du} \\$$$$\mathrm{I}\:=\:\frac{\mathrm{1}}{\mathrm{2}{i}}\int_{−\infty} ^{\mathrm{0}} \left({e}^{\left(\mathrm{1}+{i}\right){u}} −{e}^{\left(\mathrm{1}−{i}\right){u}} \right){du} \\$$$$\mathrm{I}\:=\:\frac{\mathrm{1}}{\mathrm{2}{i}}\left[\frac{{e}^{\left(\mathrm{1}+{i}\right){u}} }{\mathrm{1}+{i}}−\frac{{e}^{\left(\mathrm{1}−{i}\right){u}} }{\mathrm{1}−{i}}\right]_{−\infty} ^{\mathrm{0}} \\$$$$\mathrm{I}\:=\:\frac{\mathrm{1}}{\mathrm{2}{i}}\left[\frac{\mathrm{1}}{\mathrm{1}+{i}}−\frac{\mathrm{1}}{\mathrm{1}−{i}}\right] \\$$$$\mathrm{I}\:=\:\frac{\mathrm{1}}{\mathrm{2}{i}}\left[\frac{\mathrm{1}−{i}}{\mathrm{1}−{i}^{\mathrm{2}} }−\frac{\mathrm{1}+{i}}{\mathrm{1}−{i}^{\mathrm{2}} }\right] \\$$$$\mathrm{I}\:=\:\frac{\mathrm{1}}{\mathrm{2}{i}}\left(\frac{−\mathrm{2}{i}}{\mathrm{2}}\right)\:=\:−\frac{\mathrm{1}}{\mathrm{2}} \\$$

Answered by Smail last updated on 13/Jul/20

$${By}\:{parts} \\$$$${u}={sin}\left({lnx}\right)\Rightarrow{u}'=\frac{\mathrm{1}}{{x}}{cos}\left({lnx}\right) \\$$$${v}'=\mathrm{1}\Rightarrow{v}={x} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({lnx}\right){dx}=\left[{xsin}\left({lnx}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} −\int_{\mathrm{0}} ^{\mathrm{1}} {cos}\left({lnx}\right){dx} \\$$$${u}={cos}\left({lnx}\right)\Rightarrow{u}'=−\frac{\mathrm{1}}{{x}}{sin}\left({lnx}\right) \\$$$${v}'=\mathrm{1}\Rightarrow{v}={x} \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({lnx}\right){dx}=−\left[{xcos}\left({lnx}\right)\right]_{\mathrm{0}} ^{\mathrm{1}} −\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({lnx}\right){dx} \\$$$$\mathrm{2}\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({lnx}\right){dx}=−{cos}\left({ln}\mathrm{1}\right) \\$$$$\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({lnx}\right){dx}=\frac{−\mathrm{1}}{\mathrm{2}} \\$$

Answered by mathmax by abdo last updated on 13/Jul/20

$$\mathrm{A}\:=\int_{\mathrm{0}} ^{\mathrm{1}} \:\mathrm{sin}\left(\mathrm{lnx}\right)\mathrm{dx}\:\:\mathrm{changement}\:\mathrm{lnx}\:=−\mathrm{t}\:\mathrm{give} \\$$$$\mathrm{A}\:=−\int_{\mathrm{0}} ^{\infty} \:\mathrm{sin}\left(−\mathrm{t}\right)\left(−\mathrm{e}^{−\mathrm{t}} \right)\mathrm{dt}\:=−\int_{\mathrm{0}} ^{\infty} \:\mathrm{e}^{−\mathrm{t}} \:\mathrm{sint}\:\mathrm{dt} \\$$$$=−\mathrm{Im}\left(\int_{\mathrm{0}} ^{\infty} \:\mathrm{e}^{−\mathrm{t}+\mathrm{it}} \mathrm{dt}\right)\:\mathrm{and}\:\int_{\mathrm{0}} ^{\infty} \:\mathrm{e}^{\left(−\mathrm{1}+\mathrm{i}\right)\mathrm{t}\:} \:\mathrm{dt}\:=\left[\frac{\mathrm{1}}{−\mathrm{1}+\mathrm{i}}\mathrm{e}^{\left(−\mathrm{1}+\mathrm{i}\right)\mathrm{t}} \right]_{\mathrm{0}} ^{\infty} \\$$$$=−\frac{\mathrm{1}}{−\mathrm{1}+\mathrm{i}}\:=\frac{\mathrm{1}}{\mathrm{1}−\mathrm{i}}\:=\frac{\mathrm{1}+\mathrm{i}}{\mathrm{2}}\:\Rightarrow\:\mathrm{A}\:=−\frac{\mathrm{1}}{\mathrm{2}} \\$$

Answered by Aziztisffola last updated on 13/Jul/20

$$\:\mathrm{let}\:\mathrm{x}=\mathrm{e}^{\mathrm{t}} \:\Rightarrow\mathrm{dx}=\mathrm{e}^{\mathrm{t}} \mathrm{dt} \\$$$$\:\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({logx}\right){dx}=\int_{−\infty} ^{\:\mathrm{0}} \mathrm{e}^{\mathrm{t}} \mathrm{sin}\left(\mathrm{t}\right)\mathrm{dt}=\int_{\mathrm{0}} ^{+\infty} −\mathrm{e}^{\mathrm{t}} \mathrm{sin}\left(\mathrm{t}\right)\mathrm{dt} \\$$$$\:\mathrm{With}\:\mathrm{Laplace}\:\mathrm{transform}: \\$$$$\:\mathcal{L}\left\{−\mathrm{e}^{\mathrm{t}} \mathrm{sin}\left(\mathrm{t}\right)\right\}=\:\mathcal{L}\left\{−\mathrm{sin}\left(\mathrm{t}\right)\right\}\left(\mathrm{s}−\mathrm{1}\right)=\frac{−\mathrm{1}}{\left(\mathrm{s}−\mathrm{1}\right)^{\mathrm{2}} +\mathrm{1}} \\$$$$\:\mathrm{then}\:\int_{\mathrm{0}} ^{\:+\infty} −\mathrm{e}^{−\mathrm{st}} \mathrm{e}^{\mathrm{t}} \mathrm{sin}\left(\mathrm{t}\right)\mathrm{dt}=\frac{−\mathrm{1}}{\left(\mathrm{s}−\mathrm{1}\right)^{\mathrm{2}} +\mathrm{1}} \\$$$$\:\:\mathrm{let}\:\mathrm{s}=\mathrm{0}\:\Rightarrow\:\int_{\mathrm{0}} ^{\:+\infty} −\mathrm{e}^{\mathrm{t}} \mathrm{sin}\left(\mathrm{t}\right)\mathrm{dt}=\frac{−\mathrm{1}}{\left(−\mathrm{1}\right)^{\mathrm{2}} +\mathrm{1}}=\frac{−\mathrm{1}}{\mathrm{2}} \\$$$$\:\mathrm{Hence}\:\:\int_{−\infty} ^{\:\mathrm{0}} \mathrm{e}^{\mathrm{t}} \mathrm{sin}\left(\mathrm{t}\right)\mathrm{dt}=\frac{−\mathrm{1}}{\mathrm{2}} \\$$$$\therefore\:\int_{\mathrm{0}} ^{\mathrm{1}} {sin}\left({logx}\right){dx}=\:\frac{−\mathrm{1}}{\mathrm{2}} \\$$$$\: \\$$